TA’LĪMU MAHĀRAH AL-QIRĀ’AH MIN KHILĀLI AL MU’ALLIMĪNA AL AQRĀN FĪ AL MADRASAH AL-MUTAWASSITHAH AL-ISLAMĪYATI FATTĀHILLĀH SUMBER KERANG GENDING PROBOLINGGO LIL SANATI AL-DIRĀSĪYATI 2022\2023 M - Syamsyah, Khofifatus; Muqit, Abdul (Critical Review of English-Arabic World Journal, 2023)
Teaching methods are not only to facilitate the learning process, but also to build learning motivation, joy, fun, and comfort for female students as well. There are many methods that can be used by teachers including the peer tutor method to increase the learning motivation of female students, especially in social science lessons. Peer tutoring is one of the learning-based active teaching methods that provides opportunities and encourages female students to learn something good, and at the same time Time becomes a reference person for others. The objectives of this research are: 1) To describe the steps for teaching reading skills through peer teachers at the Islamic Middle School, Fatahillah Sumberkerang Gending Probolinggo, for the academic year 2022-2023 AD. 2) Describe the factors supporting and hindering the teaching of reading skills through peer teachers at the Fatahillah Islamic Middle School Somberkerang Gending Probolinggo for the academic year 2022-2023 AD. The research conducted by the author is embedded in qualitative research using a descriptive qualitative approach. In the process of collecting data, the author used observation, interviews, and documentation methods. The type of this research is descriptive research that produces descriptive data from people who have been observed. Data collection techniques are observation, documentation and interview. The data analysis technique in this research is data collection, data condensation, data presentation, and drawing conclusions. Data validity techniques using triangulation and source triangulation. The results of this study are: 1) The steps for implementing the peer teacher teaching method in the Fatahillah Islamic Middle School Somberkerang Gending Probolinggo include: delivering the steps and objectives for delivering the conclusions 2) The factors supporting the implementation of the peer teacher method include the interaction between teachers and students, the students’ interests, and the students’ comfort. Factors inhibiting the implementation of the peer tutor method include lack of teacher preparation, student conditions in the classroom, and inadequate infrastructure